Geography with the environmental satellites - J.P. Gastellu Etchegorry (Indonesian Journal of Geography, 1986)
Coarse spatial resolution, high temporal frequency data from the earth polar orbiting (NOAA. HACMM, Nimbus, etc.) satellites and from the geostationary (GOES. Meteosat, and GMS) satellites are presented to demonstrate their utility for monitoring terrestrial and atmospheric processes. The main characteristics of these ,satellites and of the instruments on board are reviewed. In order to be useful for environmental assessments. the remotely sensed data must be processed (atmospheric and geometric corrections, etc.). The NOAA Center provides a wide range of already processed data. such as meteorological. oceanic, hydrologic and vegetation products; o rough description of these preprocessed data is given in this article. Finally, some examples of applicotions in Southeast Asia and especially in Indonesia, are described, i.e.: agroecosystem, drought and oceanic monitoring. The paper concludes that coarse resolution, high temporal frequency ,satellite data are very valuable for environmental studies. the emphasis being laid on the improve. ment of the crop and drought assessment programmes.